2013
DOI: 10.1371/journal.pone.0067560
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Expressed by Human Airway Eosinophils after an In Vivo Allergen Challenge

Abstract: BackgroundThe mechanism for the contribution of eosinophils (EOS) to asthma pathophysiology is not fully understood. Genome-wide expression analysis of airway EOS by microarrays has been limited by the ability to generate high quality RNA from sufficient numbers of airway EOS.ObjectiveTo identify, by genome-wide expression analyses, a compendium of expressed genes characteristic of airway EOS following an in vivo allergen challenge.MethodsAtopic, mild asthmatic subjects were recruited for these studies. Induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 56 publications
5
45
0
2
Order By: Relevance
“…Consistent with these data, we found that purified human eosinophils from healthy subjects express an appreciable amount of CB 2 on mRNA (data not shown) and protein levels. Enhanced gene expression of CB 2 has been shown for lung eosinophils in allergic patients after allergen challenge 44. Accordingly, we could demonstrate that also CB 2 protein expression is significantly increased on the cell surface of peripheral blood eosinophils from symptomatic allergic donors, supporting a role for CB 2 and its ligands in the regulation of allergen‐induced eosinophilic inflammation.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with these data, we found that purified human eosinophils from healthy subjects express an appreciable amount of CB 2 on mRNA (data not shown) and protein levels. Enhanced gene expression of CB 2 has been shown for lung eosinophils in allergic patients after allergen challenge 44. Accordingly, we could demonstrate that also CB 2 protein expression is significantly increased on the cell surface of peripheral blood eosinophils from symptomatic allergic donors, supporting a role for CB 2 and its ligands in the regulation of allergen‐induced eosinophilic inflammation.…”
Section: Discussionsupporting
confidence: 62%
“…Accordingly, in the context of the induction of asthma and CAR4 expression, the gene ontology analysis of the lung tissue microarray data highlights a variety of potential functions for eosinophil CAR4, including the regulation of the keratinization, differentiation of the epithelium, and bicarbonate and anion transport. A recent microarray study from human asthmatic sputum identified a series of 57 genes characterizing airway eosinophil activation (34). Despite intriguing results and similar genome-wide approaches, this was not an eosinophil-specific approach, which may explain the absence of CAR4 on their screening list.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic ablation of EOS attenuated submucosal matrix deposition and reduced airway smooth muscle hyperplasia [17, 18]. Using genome-wide expression analyses, we recently reported that sema7A mRNA was among the transcripts that were increased in parallel with the increase of EOS in bronchoalveolar lavages (BAL) and sputum of mild allergic asthmatics following an in vivo allergen challenge [19]. While airway remodeling has been linked at least in part to the presence of EOS, their expression of sema7A has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%